Geographical Information Systems (GIS) approach for mapping the aboriginal children malnutrition growth : a case in Kemar, Perak / Haslina Hashim ... [et al.] - Haslina, Hashim; Izrahayu, Che Hashim; Suzanah, Abdullah; Fadhilah, Md Isa; Noorfatekah, Talib (2015)
Geographical Information System (GIS) has been widely used nowadays in health monitoring process throughout the whole nation. GIS also has been used to map population infectious diseases such as Dengue, Malaria and AIDS. This system has the ability to organize, manipulate, analyze and visually display spatial data and provide an efficient result thus can help the decision maker in solving the health problem. The use of GIS to map the aboriginal children malnutrition growth is thus appropriate. Children malnutrition is a multi current dimensional problem which involves with food security, education, and access to clean water, sanitation and health services. An aboriginal child is identify to be under the high risk of unhealthy growth nowadays. The factors that contribute to this issues is the living environment and sufficient of healthy food and clean water. GIS technologies have the potential to be used in mapping the children malnutrition growth and study the significance of the environment which relate to the cases. GIS has the ability to update information and visualize the result for further analysis to be taken by the bodies of interest. The objectives of this study is to identify the group of aboriginal children and their locations using global positioning systems (GPS) that need of assistance and help in health interventions, this study also provide up to date information for decision making and raise precaution awareness towards the Aboriginal Children malnutrition's problems. These malnutrition children growth results will be displayed by GIS to visualize the percentage growth. Once the result is obtained therefore further analysis can be done to monitor the aboriginal children growth with the support of healthy malnutrition program in future.